Analysis of Faults in Sewage Systems with Geographical Information Systems - Selva GÖK; Mahmut FIRAT (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Wastewater systems are one of the most important infrastructure elements in terms of human and environmental health. In such systems, failures are observed depending on various factors. These failures increase operating and maintenance-repair costs and create threats to human and environmental health. For this reason, these systems should be monitored regularly and the factors causing malfunction should be analyzed. In this study, it is aimed to evaluate and analyze failures occurring in sewerage systems with geographical information systems. For this, the failures in the sewage system of Malatya province between year 2015-2019 were taken into account. It has been determined that the most common types of failure are misuse, in-line sag and deformation, and in-line lubrication. In addition, the highest failure rate occurred in pipes with a diameter of 100-200 mm. In the spatial analysis of faults, inline collapse is generally observed in the central regions, while misuse faults are found to be in the system. It has been observed that factors such as pipe diameter and length, season, traffic load, ground feature, and improper use are effective in the increase in fault density.